Compressive creep and strength, and the carbonation of blended cement concrete containing lightweight expanded clay aggregate - Yong, Kim Wui (2019)
The objective of this research was to determine three parameters of Lightweight Concrete (LWC) containing Lightweight Expanded Clay Aggregates (LECA) in tropical climate of Singapore; Carbonation depth, compressive strength, and creep coefficients of concrete with OPC and blended cement with 50% Ground Granulated Blast furnace Slag (GGBS). All mixes were designed to meet grade 40 compressive strength. Carbonation test was accelerated by preconditioning samples in 10% CO2, 32°C and 80% humidity. Compressive strength and creep experiments were conducted in accordance to the British Standards. All mixes investigated were designed for concrete grade 40. LECA concrete had greater carbonation resistance than conventional concrete with less than 1 mm carbonation in all test periods. All the lightweight mixes obtained more than 40 MPa in compressive strength which satisfied grade 40. LECA concrete with the blended cement mixture had strain values of 839.965 μm on day 52 and the concrete with only OPC had strain values of 1134.755 μm on day 49 when put under constant loading. As a result, the concrete with blended cement mixture had creep coefficient of 0.683 at 100 years while LECA concrete had creep coefficient of 1.155.